An illustration of delays in Mucormycosis: A case Study - Toppo, Neelam Anupama; Thakur, Aditya; Soni, Deepali; Dubey, Priyanka; Tiwari, Sapna (Indian Journal of Community Health, 2021)
Background: Mucormycosis is an opportunistic fungal infection with a high fatality rate and is the third most common fungal infection that is invasive in nature, next to candidiasis and aspergillosis. It is attributed to the poor socio-economic status and triggered by the local trauma due to unhygienic setup or poor health care. The pathway of pathogenesis is not clearly understood in immunocompetent patients and therefore becomes a matter of great concern.Aim& Objective: To explore the pathway of mucormycosis in a case of post SARS-CoV-2 infection Settings and Design: Tertiary Care hospital of Jabalpur DistrictMethods and Material: Interview with the case and care taker and case file review.Results: We could conclude this as a case of rhino- orbital mucormycosis attributed to uncontrolled blood sugar during treatment of SARS-CoV-2 infection, three delays that have occurred during the disease progression like ignorance from health service provider, late diagnosis, non compliance to the advice given by health facility, poor oral and nasal hygiene and no use of distilled water in humidifier. Conclusions: The early diagnosis, prompt Treatment , surgical intervention , proper blood sugar monitoring and rational use of steroids are important steps of successful outcome of the disease.